Fig. 5. Proposed biosynthetic pathways for A in Tissue-specific localization of polyketide synthase and other associated genes in the lichen, Cladonia rangiferina, using laser microdissection - Elshobary, Mostafa E.; Becker, Michael G.; Kalichuk, Jenna L.; Chan, Ainsley C.; Belmonte, Mark F.; Piercey-Normore, Michele D. (Zenodo, 2018)
Fig. 5. Proposed biosynthetic pathways for A) atranorin according to Armaleo et al. (2008), and B) Grayanic acid according to Culberson and Armaleo (1992) and Armaleo et al. (2011). The reactions begin with esterification of the two cyclic compounds by PKS16 followed by methylation for production of atranorin and production of grayanic acid by a cytochrome P450. The dashed arrows and brackets connect each enzyme to its reaction. Published as part of Elshobary, Mostafa E., Becker, Michael G., Kalichuk, Jenna L., Chan, Ainsley C., Belmonte, Mark F. & Piercey-Normore, Michele D., 2018, Tissue-specific localization of polyketide synthase and other associated genes in the lichen, Cladonia rangiferina, using laser microdissection, pp. 142-150 in Phytochemistry 156 on page 146, DOI:10.1016/j.phytochem.2018.09.011, http://zenodo.org/record/10484507